Evaluation of Online Practical Learning for Light Automotive Engineering during the Covid-19 Pandemic - Mochammad Baharudin Siddiq; Zainal Arifin; Putu Sudira; Farid Mutohhari (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Vocational education is characterized by practical learning. During online learning in the Covid-19 outbreak, students' practice learning outcomes have decreased significantly. This study evaluates the implementation of online practical learning in Vocational High Schools (VHS) for technical competencies of Light Automotive Engineering in terms of Context, Input, Process, and Product (CIPP). This study was conducted at a Vocational High School, SMKN 1 Simpangkatis, Central Bangka Regency. The research subjects were the principal, vice-principal, 5 productive teachers, and 191 students in the department of Light Automotive Engineering. This evaluation research used the CIPP method. Data were collected through questionnaires supported with interviews and documentation. The findings indicated that (1) the implementation of online practical learning for context and input components is included in the medium category and (2) the process and product components are categorized as low.